Benthic nematodes biodiversity patterns along the gradient of the Tagus estuary (Western Coast of Portugal): Link with abundances distribution pattern of the nonindigenous bivalve Ruditapes philippinarum - Machado, marco (2017)
The non-indigenous bivalve Ruditapes philippinarum is native to the western Pacific Ocean and it has been one of the most widely introduced species for aquaculture purposes in Europe. In Portugal its presence is known in several estuaries for more than two decades and its populations have increased greatly along the last years1. Currently it’s one of the dominant benthic species in some areas of the Tagus estuary (264,1±470,8 ind./30s tow). Studies on the impacts of invasive bivalves on meiofaunal communities are scarce and restricted to the harvesting effect. Meiofauna of the Tagus estuary is poorly known and possible impacts of the introduction of R. philippinarum were never assessed.